2013
DOI: 10.1037/a0031474
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of dropout in treatments for posttraumatic stress disorder.

Abstract: Objective Many patients dropout of treatments for Post-traumatic stress disorder (PTSD) and some clinicians believe that ‘trauma focused’ treatments increase dropout. Method We conducted a meta-analysis of dropout among active treatments in clinical trials for PTSD (42 studies; 17 direct comparisons). Results The average dropout rate was 18%, but it varied significantly across studies. Group modality and greater number of sessions, but not trauma focus, predicted increased dropout. When the meta-analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

51
383
11
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(451 citation statements)
references
References 77 publications
(93 reference statements)
51
383
11
6
Order By: Relevance
“…Arguably, the lack of effect in previous treatments might (also) be associated with the high dropout rates, running up to 52% for conventional PTSD interventions (Imel et al, 2013). In the present study, all participants completed the intensive phase and few patients (5%) left the booster phase prematurely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arguably, the lack of effect in previous treatments might (also) be associated with the high dropout rates, running up to 52% for conventional PTSD interventions (Imel et al, 2013). In the present study, all participants completed the intensive phase and few patients (5%) left the booster phase prematurely.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this suboptimal response, dropout rates in regular TFT programmes are high. A meta-analysis investigating dropout from PTSD treatment, including TFT programmes and supportive counselling (Imel, Laska, Jakupcak, & Simpson, 2013), estimated that, on average, 18% of patients drop out, with percentages varying significantly across studies and rates running up to 52%, although definitions of dropout differed among the studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this perspective, the drop-out rate in the current study of less than 4% is a remarkable finding. This is even more remarkable as regular treatment programmes for PTSD report drop-out rates of approximately 20% (Imel, Laska, Jakupcak, & Simpson, 2013), given the discussion about the need for a stabilization and emotion regulation phase (De Jongh et al, 2016) and the prevailing notion that a history of CSA renders patients more prone to attrition (Cloitre et al, 2002). However, the reason for the low drop-out rate may also be due to more practical aspects of intensive treatment, since within a short time-frame of two weeks less interfering variables may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Only 40% of military veterans lose their PTSD diagnosis after receiving trauma-focused treatment (Bradley et al, 2005; Steenkamp, Litz, Hoge, & Marmar, 2015). Imel, Laska, Jakupcak, and Simpson (2013) found an average dropout of 18% among 44 studies, yet indicated that dropout rates varied quite dramatically across studies. Schottenbauer, Glass, Arnkoff, Tendick, and Gray (2008) described a range of studies in their review, including small sample studies and non-controlled studies, and identified a broad range of dropout from 0 to 54% and non-responders ranging from 0 to 89%.…”
mentioning
confidence: 99%